Dakwah dan Bisnis: Strategi Komunikasi PT Herba Penawar Alwahida Indonesia dalam Mencetak Wirausahawan Muslim - Minangsih, Kalsum (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study aims to analyze the communication strategies used by PT HNI HPAI in developing Muslim entrepreneurship in Indonesia. The research method employed a qualitative approach with descriptive techniques. Data obtained from the company were systematically processed, including written, archived, and oral data, as well as observed behavior, to obtain information relevant to the research title. The findings of this study indicate that PT HNI HPAI's communication strategy in developing Muslim entrepreneurship in Indonesia utilizes a persuasive strategy. The company encourages Muslims to migrate to a lifestyle, or in other words, to adopt local Muslim products and adopt medical or health methods. This research contributes to the development of persuasive communication studies in the context of da'wah and entrepreneurship. It also provides a concrete illustration of effective communication strategies for fostering a network of Sharia-based Muslim entrepreneurs.